Keep writing: the critique of the university in Roberto Bolaño's 2666. Issue 5 (28th July 2016) - Eve, Martin Paul
ABSTRACT: Roberto Bolaño's 2666 is a novel that can be situated, aesthetically, within the traditions of utopian fiction and the North American encyclopaedic, postmodern novel. It is also, however, a text that is exemplary of a type of didacticism that cloaks its mechanism behind an overloaded structure. One of the explicit targets of this didacticism is the neo-liberal university that, in 2666, is structurally twinned with the police department and is thus complicit in the novel's femicides. This article suggests the ways in which Bolaño's novel attempts to discipline the academy while also outlining its mode of crypto-didacticism. Taking theoretical cues from Theodor W. Adorno and Pierre Bourdieu, this article reads 2666 as a metafictional work that signals its own desire to teach, thereby representing a fresh approach for ethics in the postmodern novel and beyond.